Microbiomes in the context of insect communities - Brown, Joel James (Jihočeská univerzita, 2021)
The aim of this thesis was to investigate the deterministic patterns of insect-associated microbiome community composition and to investigate the role of symbiotic bacteria in insect model systems. I have shown that life stage is a key factor influencing microbiome composition, in both holometabolous and hemimetabolous insects, in addition to host species identity and local environment. I was able to find these deterministic patterns by controlling for diet in field studies of microbiomes, which is a well-known influential factor of microbiome communities. My thesis emphasises the importance of investigating the taxonomic and functional diversity of insect microbiomes and including symbiotic microbes in community level studies.
Microbiomes in the context of insect communities
Keywords: Microbiome; symbiosis; insect; community; ecology; symbiont; bacteria; Drosophila; parasitoid; triatomine; climate change; Microbiome; symbiosis; insect; community; ecology; symbiont; bacteria; Drosophila; parasitoid; triatomine; climate change